Penerapan Model Pembelajaran Problem Based Learning untuk Meningkatkan Motivasi Belajar di Kelas VIII SMP Negeri 2 Sungai Kunyit - Delsepin, Adriani; Role, Metoddyus Tri Brata; Lisarani, Varetha (Vocat : Jurnal Pendidikan Katolik, 2024)
This study was conducted to enhance the learning motivation of Grade VIII students at SMPN 2 Sungai Kunyit in the subject of Catholic Religious Education (PAK), which was deemed low. The study employed the Problem-Based Learning (PBL) model as an intervention. Classroom Action Research (CAR) was conducted in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. The subjects of the study were 10 Grade VIII students at SMPN 2 Sungai Kunyit for the 2023/2024 academic year. Data were collected through observation sheets and student motivation questionnaires. The results showed a significant increase in student learning motivation from the pre-cycle, Cycle I, to Cycle II. In the pre-cycle stage, students' learning motivation reached only 30%. During Cycle I, learning motivation dropped to 20% due to suboptimal implementation of the model, with the success indicator set at 80%. After reflection and improvements, in Cycle II, students' learning motivation sharply increased to 90%. In conclusion, the application of the Problem-Based Learning model proved effective in enhancing students' learning motivation in the material "Jesus Proclaims the Kingdom of God Through Actions or Miracles" in Grade VIII at SMPN 2 Sungai Kunyit.